Oral presentation anxiety among undergraduate Malaysian Chinese students in a private university - Fong, Yi An; Latha Ravindran,; Ghayth Kamel Shaker Al-Shaibani, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research investigates presentation anxiety among undergraduate Malaysian Chinese students in a private university where English language is used as a medium of instruction in private universities in Malaysia. There is little research on the difficulties in the teaching and learning such as presentation anxiety among ESL (English as a Second Language) Malaysian Chinese students. The objectives of this study are to explore the different levels of presentation anxiety and to identify coping strategies used by the students with English-speaking anxiety among undergraduate Malaysian Chinese students in a private university. Hence, a mixed method approach is used which involves a questionnaire and semi-structured interview. Sixty participants responded to the English Language Classroom Anxiety Scale (ELCAS) questionnaire and six interviewees who took part in the questionnaire were purposively chosen to conduct the interview. ELCAS Quantitative results indicated that ESL Malaysian Chinese students in the private university showed moderate levels of presentation anxiety when doing presentations. As for the qualitative data, the findings revealed that students often rehearse and practice before their presentation to cope with the existing anxiety. We suggest that language instructors are to deliver a more positive learning environment and to provide adequate guidance in class to improve the presentation skills and speaking skills among ESL Malaysian Chinese students as well as other ESL and EFL (English as Foreign Language) students.